Assessing Arabic language learning for deaf student: a study of using mobile immersion in Saudi Arabia - Jamaan, Jawaher; Abdullah, Zainatul Shima (Institute of Electrical and Electronics Engineers Inc., 2018)
This study focuses on using m-learning in Arabic language learning for deaf student. A thorough planning has been organized on the methodology and the study research sequence, to ensure smooth organization of the research. The methodology of this research contains three sections. The first section is on the sample/participants chosen for the study, the second section focuses on the research design/procedures used in conducting the study and the third section is on the research experimental method. Finding of study showed that there is statistically significant difference between total scores before/pretest and total scores after/posttest in intervention program of writing skills for deaf students. © 2018 IEEE.